2005
DOI: 10.1016/j.jana.2005.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of People Living With HIV Who Use Community-Based Services in Ontario, Canada: Implications for Service Providers

Abstract: Community-based AIDS service organizations (CBAOs) direct services to multiple-needs people living with HIV/AIDS who are less likely to use mainstream health promotion services. As people live longer with HIV, the potential to enhance quality of life increases, yet little is known about who uses CBAOs or how this use affects other health and social services. This study of people living with AIDS in Ontario, Canada (n = 297) examined the demographic and health-related characteristics of people with AIDS who do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
1
8
0
1
Order By: Relevance
“…This study’s observed prevalence of clinically significant depressive symptoms was comparable to a sample of PLWHA who attended community-based AIDS service organizations in Ontario, Canada (Williams, Narciso, Browne, et al, 2005). Given the elevated prevalence of depression in PLWHA, and more so among PLWHA smokers and in PLWHA using community-based services, these findings would be expected (Williams, et al, 2005).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This study’s observed prevalence of clinically significant depressive symptoms was comparable to a sample of PLWHA who attended community-based AIDS service organizations in Ontario, Canada (Williams, Narciso, Browne, et al, 2005). Given the elevated prevalence of depression in PLWHA, and more so among PLWHA smokers and in PLWHA using community-based services, these findings would be expected (Williams, et al, 2005).…”
Section: Discussionsupporting
confidence: 57%
“…Given the elevated prevalence of depression in PLWHA, and more so among PLWHA smokers and in PLWHA using community-based services, these findings would be expected (Williams, et al, 2005). …”
Section: Discussionmentioning
confidence: 96%
“…First, our study participants are primarily individuals affiliated with or receiving services from community-based AIDS service organizations, which limits the generalizability of our findings to those accessing these services. Individuals receiving services from community-based AIDS service organizations, for example, are more likely to report physical disability, difficulty sustaining normal activities, being depressed and poor HRQOL compared to those who do not receive services from these providers [46]. Second, participants who completed the 1-year follow-up were less likely to: be homeless or inadequately housed, report a history of homelessness, to move frequently, and report a history of incarceration at baseline than those who were lost-to-follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…10 3.3. Access and Support Available from within the Health Care Sector Messeri et al (2002) and Williams et al (2005) are of the opinion that access to ancillary services may be particularly important in supporting frontline medical care provided to persons living with HIV and in enhancing the QOL of PLWA. SHC i represents a vector of binary variables representing care and support available to individual i within the health care sector, both directly related to the ART programme, but also to the broader health care sector.…”
Section: The Heart In Haartmentioning
confidence: 99%